Understanding Purchase Intentions and Decisions for Isotonic Beverages: The Role of Motivation, Lifestyle, and Word of Mouth - Megawati Simanjuntak; Virna Keryn Patricia Hutajulu (Jurnal Perilaku dan Strategi Bisnis, 2024)
One way to maintain fluid balance in the body is by consuming isotonic beverages. This study aims to analyze the influence of motivation, lifestyle, and word of mouth on purchase intention, as well as the influence of motivation, lifestyle, word of mouth, and purchase intention on the purchase decision for isotonic beverages. The study employed a non-probability sampling method with a census technique. The research population consisted of students participating in 10 sports extracurricular organizations (UKM). Data were collected through a survey using questionnaires distributed to 225 student members of sports UKM. Data analysis was conducted using SPSS and SEM. The results of the study indicate that motivation, lifestyle, and word of mouth have a significant positive effect on purchase intention. Furthermore, the findings also show that motivation, lifestyle, and purchase intention significantly influence the purchase decision for isotonic beverages.